PERLINDUNGAN DAN UPAYA HUKUM BAGI PEKERJA KARENA PEMUTUSAN HUBUNGAN KERJA SEPIHAK - Ida Bagus Kade Putra Manuaba; Ida Ayu Sadnyini (Universitas Pendidikan Nasional, 2018)
The Industrial Relationship Pancasila as orientation of philosophy for the labor law, have a purpose to balancing the right and obligation of labor, industrialist and government. Issues in this research are how represif and prefentif legal protection and legal efforts for employees cause unilateral termination as result of heavy mistake according to Act Number 13 Year 2003 concerning Labor. The purpose of this research is to know and examines the legal protection and the legal efforts for employees cause unilateral termination. The conclusion from this researchthat the substace of regulation on legal protection for unilateral termination as result of heavy mistake, is not formulated yet clearly and comprehensiveness with the result that legal uncertainty for laborer. And then for resolve the conflict there is 2 alternative dispute resolution, with litigation process pass through the court or non litigation process.Keyword: Act Number 13 Year 2003 Concerning Labor, Article 158, Industrial Relationship, Termination.